Metronomic oral topotecan prolongs survival and reduces liver metastasis in improved preclinical orthotopic and adjuvant therapy colon cancer models. Issue 2 (28th April 2012) - Hackl, Christina; Man, Shan; Francia, Giulio; Milsom, Chloe; Xu, Ping; Kerbel, Robert S
Abstract : Objective: Advanced and recurrent diseases are the major causes of death in colon cancer. No standard preclinical model addresses advanced disease and spontaneous metastasis after orthotopic tumour growth. In this study, the authors report the establishment of such standardised orthotopic mouse models of colon cancer and their use in evaluating metronomic topotecan alone or in combination with standard chemotherapy. Design: Human colon cancer cell lines, transfected with human chorionic gonadotropin and luciferase, were injected orthotopically into the caecal wall of severe combined immunodeficient mice, intrasplenically or subcutaneously. For adjuvant therapy, caecal resections were performed 3–5 weeks after tumour cell injection. Chemotherapy drugs tested included uracil/tegafur, folinic acid, oxaliplatin, topotecan, pazopanib and various combinations. Results: Subcutaneous tumours showed exaggerated sensitivity to treatment by delayed tumour growth (p = 0.002) and increased survival (p = 0.0064), but no metastatic spread. Intrasplenic cell injection resulted in rapid and extensive but artefactual metastasis without treatment effect. Intracaecal cell injection with tumour take rates of 87.5–100% showed spontaneous metastases at clinically relevant rates. Metronomic topotecan significantly polonged survival and reduced metastasis. In the adjuvant setting, metronomic maintenance therapy (after FOLFOX-like induction) prolonged survival compared with vehicle controls (p=0.0003), control followed by topotecan (p=0.0161) or FOLFOX-like therapy (p=0.0003). Conclusion: The refined orthotopic implantation technique proved to be a clinically relevant model for metastasis and therapy studies. Furthermore, metronomic therapy with oral topotecan may be promising to consider for clinical trials of metastatic colon cancer and long-term adjuvant maintenance therapy of colon cancer.